Fatigue performance of long-term aged crumb rubber modified bitumen containing warm-mix additives. (10th April 2020) - Wang, Haopeng; Liu, Xueyan; van de Ven, Martin; Lu, Guoyang; Erkens, Sandra; Skarpas, Athanasios
Highlights: This study compared different fatigue characterization methods for binders. Time sweep test measured fatigue life was compared with the linear amplitude sweep test predicted fatigue life. The effects of rubber content and warm-mix additives on the binder fatigue performance were investigated and analyzed. Abstract: Recently warm mix asphalt (WMA) technologies have been introduced to rubberized asphalt mixtures to decrease the required construction temperatures and to alleviate the hazardous gas emissions. Rubberized asphalt pavements combining with WMA have the potential to improve the long-term pavement performance. This study aims to investigate the fatigue performance of crumb rubber modified bitumen (CRMB) containing warm-mix additives using different characterization methods. The effects of crumb rubber modifier (CRM) content (5%, 10%, 15% and 22% by weight of base bitumen) and warm-mix additives on the binder fatigue performance were investigated. Various laboratory tests, including frequency sweep tests, time sweep (TS) tests and linear amplitude sweep (LAS) tests, were conducted on the long-term aged binders to obtain indicators of fatigue performance. Results show that there is a good correlation between the measured fatigue life determined by TS tests using the dissipated energy concept and the predicted fatigue life determined by LAS tests using the simplified viscoelastic continuum damage (S-VECD) theory. However, the traditional Superpave fatigue parameter and the G-R parameter cannot characterize accurate enough the fatigue performance of modified binders. CRMB binders exhibit superior fatigue performance compared to the neat bitumen. The effects of warm-mix additives on the fatigue performance are different for neat bitumen compared to CRMB binder. Based on the findings in this study, rubberized asphalt mixture combining with WMA additives is expected to have a promising long-term fatigue performance.